ENT 600 : New product development : Convenient thermos (CT) / Muhammad Nizamul Hakim Norzaki ... [et al.] - Hakim Norzaki, Muhammad Nizamul; Awg Osman, Dygku Aniqnatasa; Arzman, Nuriman Aimi; Zainol, Nur Syuhada (2019)
DINS EZ Sdn. Bhd. is a company form by four members and planning to develop Convenient Thermos (CT). • This product is idealized from personal experience and existing product in market. • CT is a plugless thermos that can reheat user's drink to meet desired water temperature which is 40°C. • It also can reheat the drink more than 100 times depends on the capacity of power bank. • There are four unique features of CT: (i) USB port: As an alternative to replace electric socket (ii) Switch: To turn On or Off the thermos heater (iii) Alarm: Alert user when the drink meets desired water temperature which is 40°C. (iv) Liquid Cristal Display (LCD): Display temperature of drink (v) Power bank: 5V output of power bank can supply power to thermos • Below shows the list of objectives of this product: a) To help employee reduce expenses by bring hot or warm drink water from home. b) To maintain temperature of user drink more than two hours c) To reheat the drink when it's temperature below than 30°C